THE RELEVANCE OF TA'LIMUL MUTA'ALLIM TEACHINGS TO CHARACTER EDUCATION OF RELIGIOUS PROGRAMS IN THE ERA OF SOCIETY 5.0 - Sulusiyah, Sulusiyah; Alwi, Bashori (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study examines the relevance of Ta'limul Muta'allim teachings in character education in the Religious Program of MAN 1 Probolinggo in the Society 5.0 era. This study used qualitative methods to collect data through field observations and interviews with teachers, students, and related parties. The study results indicate that integrating technology in character education can strengthen the internalization of moral and ethical values contained in the teachings of Ta'limul Muta'allim. Technology allows broader access to learning resources and more interactive learning experiences, but technology also requires supervision so as not to interfere with students' focus. In addition, applying an interdisciplinary approach, which integrates moral values in various disciplines, has proven effective in enriching character learning in dormitories and classrooms. This study suggests developing a more adaptive technology-based character education model and strengthening training for teachers and musyrifah to use technology wisely in the character learning process.